THE RELEVANCE OF BRACKETING COAL POWDER USING A PISTON PRESS (Web of Technology: Multidimensional Research Journal, 2024)
This study focuses on the development and application of a high-pressure piston press to enhance the usability of coal dust generated during mining and transportation processes. Coal dust, a byproduct often considered waste, poses significant environmental and safety challenges. By implementing a bracketing technique through a piston press, the study aims to compact coal powder into a more manageable and functional form, suitable for industrial and domestic applications. The designed press utilizes advanced materials and engineering principles to withstand high-pressure conditions, ensuring efficient compaction while minimizing energy consumption. Experimental results demonstrate the potential of this technology to reduce waste, improve coal utilization, and mitigate environmental impacts. The findings are significant for industries seeking sustainable and efficient coal management solutions, providing a pathway for resource optimization and environmental conservation.